Urban Qur’anic Learning and Religious Meaning in Majelis Taklim Kalam - Arifudin Arifudin; Sutrisno Sutrisno; Muhammad Chirzin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
Urban Muslim communities increasingly require flexible religious learning spaces that can combine Qur’anic literacy, social care, and contextual guidance. This study examines Majelis Taklim Kalam Yogyakarta as a nonformal Qur’anic learning institution by focusing on how institutional governance, pedagogical practice, and congregational interaction shape religious meaning among adult and elderly congregants. Using a qualitative single embedded case study, data were collected through participant observation in regular study sessions, in-depth interviews with instructors, administrators, and congregants, and analysis of institutional documents, learning materials, attendance records, and monitoring forms. The findings show that organizational restructuring under the Obor Pencerah Kalbu Foundation strengthens administrative clarity, learning continuity, and congregational access, but also creates risks of bureaucratization and uneven implementation across learning sites. Pedagogically, the integration of mushafi, nuzuli, and maudhu’i approaches enables gradual, contextual, and reflective engagement with the Qur’an. Socially, dialogical interaction produces spiritual solidarity, emotional support, and ethical reorientation, especially among elderly participants. This study contributes an integrated model of urban Qur’anic learning that links institutional structure, contextual pedagogy, and social interaction, with implications for andragogical training, intergenerational participation, and policy support for nonformal Islamic education.